A Novel Visible‐Light‐Responsive Semiconductor ScTaO4−xNx for Photocatalytic Oxygen and Hydrogen Evolution Reactions. Issue 1 (28th September 2020) - Pei, Lang; Cai, Hong; Jin, Hao; Li, Taozhu; Zhu, Heng; Yuan, Yongjun; Zhong, Jiasong; Yan, Shicheng; Zou, Zhigang
Abstract: Screening of visible‐light‐responsive semiconductor photocatalysts is a significant target for solar water splitting systems. Herein, a newly designed Ta‐based oxynitride, namely ScTaO4−x Nx, was successfully synthesized via nitrogen doping of ScTaO4 oxide precursors at 1273 K under NH3 flow. The ScTaO4−x Nx photocatalyst, with a strong band‐to‐band visible light absorption as far as 540 nm, can be employed for both water oxidation and reduction half‐reactions under visible light illumination, demonstrating great potential for photocatalytic water splitting. Abstract : Photocatalysis : A nitrogen‐doped tunable tunneled oxide ScTaO4−x Nx with an absorption edge of ca. 540 nm is identified as a narrow bandgap bifunctional photocatalyst for photocatalytic OER and HER.